The Infection Route of Tomato Zonate Spot Virus in the Digestive System of Its Insect Vector Frankliniella occidentalis - Chen, Yong; Liu, Yuyan; Wang, Liang; Li, Heng; Linghu, Tingting; Chen, Yixin; Tian, Houjun; Lin, Shuo; Zheng, Xue; Wei, Hui (Frontiers in Microbiology, 2022)
Tomato zonate spot virus (TZSV) is a phytopathogen of the genus Orthotospovirus (Bunyaviridae) that is widespread in many areas of Southwest China. TZSV is mainly transmitted by Frankliniella occidentalis, but its exact infection route remains unclear. To explore this issue, we detected the nucleocapsid protein of TZSV in the digestive systems of first-instar F. occidentalis nymphs fed with TZSV-infected pepper leaves. TZSV infection in the F. occidentalis digestive system begins within 4 h post-first access to diseased plants: The foregut is likely the primary site of infection, and primary salivary glands (PSGs) are the destination. There are three potential routes for TZSV transmission from the alimentary canal to the PSGs: (1) virus dissemination from the midgut to hemocoel followed by movement to the PSGs; (2) accumulation in midgut epithelial cells and arrival at PSGs via tubular salivary glands and efferent ducts; and (3) arrival at epitheliomuscular cells of the forepart of the midgut and movement along the ligament to the PSGs. We tested the transmission efficiency of F. occidentalis in second-instar nymphs and female and male adults. TZSV was transmitted in a persistent-propagative mode by both nymphs and adults, with adults appearing to show slightly higher transmission efficiency than nymphs. We confirmed the presence of all three routes for TZSV transmission in F. occidentalis and determined that like other Orthotospoviruses, TZSV is transmitted in a persistent-propagative manner. These results should facilitate the control of TZSV-related diseases and further our understanding of the transmission biology of Orthotospoviruses in general.